2021
DOI: 10.3389/fpls.2021.681283
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the Peach Transcription Factor Early Bud-Break 1 Leads to More Branches in Poplar

Abstract: Shoot branching is an important adaptive trait that determines plant architecture. In a previous study, the Early bud-break 1 (EBB1) gene in peach (Prunus persica var. nectarina) cultivar Zhongyou 4 was transformed into poplar (Populus trichocarpa). PpEBB1-oe poplar showed a more branched phenotype. To understand the potential mechanisms underlying the EBB1-mediated branching, transcriptomic and proteomics analyses were used. The results showed that a large number of differentially expressed genes (DEGs)/diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…In contrast, the transcript levels of RAX1, which encodes an MYB transcription factor involved the initiation of axillary meristems ( Jia et al, 2020) were increased in SAP11-Ri. Furthermore, the expression levels of DML10, a gene involved in bud break (Conde et al, 2019), and CYP707A, a gene related to bud dormancy (Zhao et al, 2021), were also upregulated in SAP11-Ri. However, the mRNA abundance of DRM, a marker of bud dormancy (Yoon et al, 2017), was decreased in SAP11-Ri compared with the WT plants (Figure 5).…”
Section: Discussionmentioning
confidence: 98%
“…In contrast, the transcript levels of RAX1, which encodes an MYB transcription factor involved the initiation of axillary meristems ( Jia et al, 2020) were increased in SAP11-Ri. Furthermore, the expression levels of DML10, a gene involved in bud break (Conde et al, 2019), and CYP707A, a gene related to bud dormancy (Zhao et al, 2021), were also upregulated in SAP11-Ri. However, the mRNA abundance of DRM, a marker of bud dormancy (Yoon et al, 2017), was decreased in SAP11-Ri compared with the WT plants (Figure 5).…”
Section: Discussionmentioning
confidence: 98%
“…In shoot branching, sugar signals are more strongly involved in activation of dormant buds than in seasonal growth, sugar fluxes can mimic decapitation effects, and sugars rapidly accumulate in axillary buds after decapitation [33]. A recent study showed that the overexpression of the peach Early bud‐break 1 ( PpEBB1 ) gene in poplar leads to the formation of more branches by differentially regulating the genes and proteins involved in light response, brassinosteroid signaling and nitrogen metabolism [17]. Further analysis of PpEBB1oe plants also revealed the accumulation of various sugars, such as fructose, glucose, sucrose, trehalose and starch, which were correlated with an increased number of branches.…”
Section: Sugars: Signalling Molecules or Simply Energy Sources In Bra...mentioning
confidence: 99%
“…These plants present several advantages for their investigation, including a short life cycle, available genome sequences, wellunderstood genetic properties and a convenient size [11][12][13]. However, they cannot provide information on key aspects of perenniality, and so, in recent years, studies have been extended to many perennial model systems, such as Arabis alpina, rose, apple, grapevine, peach, and several species and hybrids of Populus (hereafter poplars) [14][15][16][17][18][19][20][21]. In many of the plants noted above, studies of shoot branching regulation have focused on the effects of apical dominance on branching, largely in classical decapitation experiments, rather than effects of seasonal regulation, and so the key questions remain unanswered.…”
Section: Introductionmentioning
confidence: 99%
“…Bud mutation is an important means of causing changes in branching through plant somatic variation ( Zhao et al., 2021 ). The meristem cells of buds undergo genetic changes during cell division, leading to the development of lateral branches ( Leng et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%